Convergence of iterative schemes for solving fixed point problems for multi-valued nonself mappings and equilibrium problems - Watcharaporn Cholamjiak (2018)
© 2015 All rights reserved. In this paper, we use the viscosity approximation method to establish strong convergence theorems for a finite family of nonexpansive multi-valued nonself mappings and equilibrium problems in a Hilbert space under some suitable conditions. As applications, we provide an example and numerical results.